Analytical methodologies for sensing catechol-O-methyltransferase activity and their applications - Fang-Yuan Wang; Ping Wang; Dong-Fang Zhao; Frank J. Gonzalez; Yu-Fan Fan; Yang-Liu Xia; Guang-Bo Ge; Ling Yang (Elsevier, 2021)
Mammalian catechol-O-methyltransferases (COMT) are an important class of conjugative enzymes, which play a key role in the metabolism and inactivation of catechol neurotransmitters, catechol estrogens and a wide range of endobiotics and xenobiotics that bear the catechol group. Currently, COMT inhibitors are used in combination with levodopa for the treatment of Parkinson's disease in clinical practice. The crucial role of COMT in human health has raised great interest in the development of more practical assays for highly selective and sensitive detection of COMT activity in real samples, as well as for rapid screening and characterization of COMT inhibitors as drug candidates. This review summarizes recent advances in analytical methodologies for sensing COMT activity and their applications. Several lists of biochemical assays for measuring COMT activity, including the probe substrates, along with their analytical conditions and kinetic parameters, are presented. Finally, the challenges and future perspectives in the field, such as visualization of COMT activity in vivo and in situ, are highlighted. Collectively, this review article overviews the practical assays for measuring COMT activities in complex biological samples, which will strongly facilitate the investigations on the relevance of COMT to human diseases and promote the discovery of COMT inhibitors via high-throughput screening.